How Neoliberal Imperialism is Expressed by Programming Strategies of Phoenix TV: A Critical Case Study (Global Media Journal - German Edition, 2013)
This project is a case study of Phoenix Television, which is a Hong Kong-based satellite TV network broadcasting to the global Chinese-speaking community, primarily to the mainland of China. In the theoretical framework of media imperialism and neoliberal imperialism, this study focuses on the programming strategies of Phoenix TV and examines how the global trend of neoliberalism, the Chinese government’s tight control of the media, and the sophisticated ownership of Phoenix TV intertwined to influence on its programming. The analysis of the format, content, naming, and scheduling reveals that US-inspired neoliberalism is expressed in the network’s programming strategies. This expression, in fact, is the balance that Phoenix found between the tension of global and Chinese interests, the tension between revenue making and public service, and the tension between Party-control and profit seeking.
Keywords: Television; TV programming; Phoenix TV; Neoliberal Imperialism